National direct-drive program on OMEGA and the National Ignition Facility. (18th October 2016) - Goncharov, V N; Regan, S P; Campbell, E M; Sangster, T C; Radha, P B; Myatt, J F; Froula, D H; Betti, R; Boehly, T R; Delettrez, J A; Edgell, D H; Epstein, R; et al.
Abstract: A major advantage of the laser direct-drive (DD) approach to ignition is the increased fraction of laser drive energy coupled to the hot spot and relaxed hot-spot requirements for the peak pressure and convergence ratios relative to the indirect-drive approach at equivalent laser energy. With the goal of a successful ignition demonstration using DD, the recently established national strategy has several elements and involves multiple national and international institutions. These elements include the experimental demonstration on OMEGA cryogenic implosions of hot-spot conditions relevant for ignition at MJ-scale energies available at the National Ignition Facility (NIF) and developing an understanding of laser-plasma interactions and laser coupling using DD experiments on the NIF. DD designs require reaching central stagnation pressures in excess of 100 Gbar. The current experiments on OMEGA have achieved inferred peak pressures of 56 Gbar (Regan et al 2016 Phys. Rev. Lett .117 025001). Extensive analysis of the cryogenic target experiments and two- and three-dimensional simulations suggest that power balance, target offset, and target quality are the main limiting factors in target performance. In addition, cross-beam energy transfer (CBET) has been identified as the main mechanism reducing laser coupling. Reaching the goal of demonstrating hydrodynamic equivalence on OMEGA includes improving laser power balance, target position, and target quality at shot time. CBET must also be significantly reduced and several strategies have been identified to address this issue.